Disturbances of energy metabolism in the internal organs in traumatic cranial injury on the background of diabetes - V. M. Meretskyі (Zaporožskij Medicinskij Žurnal)
Traumatic cranial injury is one of the leading reasons in the statistics of mortality. Modern ideas about the pathogenesis of traumatic brain injury based on the allocation of primary and secondary factors of brain damage. One of the main causes of secondary brain injury is hypoxia – insufficient provision with oxygen. Changes in oxygen balance lead to activation of oxidative stress, disturbances of mitochondria membranes and their death, and progression of energy metabolism imbalance caused by trauma. Millions of people worldwide suffer from diabetes mellitus. One of the factors that influences the development of complications of diabetes, is an accumulation of highly toxic peroxide compounds that intensify the processes of destabilization of cell membranes. Further research of peculiarities of oxidative stress and energy metabolism imbalance in diabetes associated with trauma will provide the basis for therapeutic directions to increase treatment options and improve patient health and well-being.